Nontypeable Hemophilus influenzae (NTHi) Septic Arthritis of Atypical Joints With Tenosynovitis in a Healthy Adult - Fatema Ravat; Gul Madison (Annals of Internal Medicine: Clinical Cases)
Hemophilus influenzae septic arthritis is uncommon in the postvaccine era, but cases caused by nontypeable strains (NTHi) are rising in adults. A healthy 47-year-old African American man presented with bilateral wrist pain, swelling, and back pain. A computed tomography scan of the chest revealed pneumonia; however, he had no respiratory symptoms. Blood cultures grew NTHi. Magnetic resonance imaging revealed bilateral wrist tenosynovitis, sacroiliac joint septic arthritis, and piriformis abscess. He required surgical joint washout and prolonged intravenous antibiotics. This case highlights the evolving epidemiology of NTHi, its potential for invasive infections in healthy individuals, and the need for early recognition and thorough diagnostic evaluation in atypical presentations.